Effect of the Guar Gum Concentration on Organoleptic Characteristics Jelly Drink Galoba - Priscilia Picauly (Universitas Pattimura, 2022)
he aim of the study was to characterize the organoleptic parameters tested were hedonic testing and hedonic quality including color, taste, texture, suction power. The result of the jelly drink organoleptic test was analyzed descriptively. Based on the result of the study, the organoleptic characteristics of the galoba jelly drink, namely for the hedonic test, the color ranged from 2.8 – 3.1 (close to somewhat like to somewhat like), taste 4.0-4.1 (like), texture 3.5-4.0 (rather like to like), suction power ranged from 3.6 -4.0 (rather like to like), and hedonic quality test for color 2.6-3.0 (close to cloudy white – slightly cloudy white), taste 3.5-3.6 (slightly galoba taste), texture 2.8 – 4.0 (textured close to slightly chewy to chewy), and suction power 3.6-4.0 (rather easy to suck up to easy to suck up).